2003
DOI: 10.1097/01.asn.0000099383.57934.0e
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Mechanisms of Cyclosporin A–Induced Tubular Cell Apoptosis

Abstract: ABSTRACT. Tubular cell apoptosis contributes to the pathogenesis of renal injury. However, the intracellular pathways that are active in tubular epithelium are poorly understood. The lethal pathways activated by cyclosporin A (CsA), a nephrotoxin that induces caspase-dependent apoptosis in tubular epithelium, were explored. Fas expression, caspase activation, and mitochondrial injury were assessed by Western blot, flow cytometry, and microscopy in cultured murine tubular epithelial cells exposed to CsA. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
115
2
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 122 publications
(129 citation statements)
references
References 29 publications
9
115
2
3
Order By: Relevance
“…65 CsA increases Fas expression in tubular cells in culture and in vivo 66,67 ; however, neither neutralizing anti-FasL antibodies nor caspase-8 inhibitors decrease apoptosis induced by CsA. 67 Similar observations were made with acetaminophen. 68 This suggests some changes in apoptosis-related molecules are epiphenomena not directly related to cell death.…”
Section: Nephrotoxins Illustrate Intracellular Death Pathwayssupporting
confidence: 64%
See 1 more Smart Citation
“…65 CsA increases Fas expression in tubular cells in culture and in vivo 66,67 ; however, neither neutralizing anti-FasL antibodies nor caspase-8 inhibitors decrease apoptosis induced by CsA. 67 Similar observations were made with acetaminophen. 68 This suggests some changes in apoptosis-related molecules are epiphenomena not directly related to cell death.…”
Section: Nephrotoxins Illustrate Intracellular Death Pathwayssupporting
confidence: 64%
“…By contrast, Bax-mediated mitochondrial injury and caspase activation are key events in CsA-induced apoptosis of tubular cells. 67,69,70 CsA induces Bax aggregation and translocation to mitochondria, causing permeabilization of the outer mitochondrial membrane, re-lease of cytochrome c and SMAC/DIA-BLO, and activation of caspase-9 and -3. Initiator caspase-2 is also activated and may lead to mitochondrial injury.…”
Section: Nephrotoxins Illustrate Intracellular Death Pathwaysmentioning
confidence: 99%
“…Taking into account the amount of cells and volumes used in the assays with CsA and that 1 × 10 6 hPT cells has about 1 mg of protein [30,32], the concentration of CsA used here to assess the role of the MPT in DCVC-induced cytotoxicity was approximately 0.8 μM. In contrast, Justo et al [38] demonstrated renal tubular cell apoptosis at CsA concentrations of 0.8 to 8 mM, which is three-to four-orders of magnitude higher than the concentration used here. Hence, CsA-induced cytotoxicity was not a confounding effect in the present studies.…”
Section: Experimental Designmentioning
confidence: 98%
“…Thus, cyclosporine A (CsA) was used to block the mitochondrial membrane permeability transition (MPT), ruthenium red (RR) was used to inhibit the calcium uniporter, thereby preventing calcium ion cycling, and PK11195 [1-(2-chlorophenyl)-N-(1-methylpropyl)-3-isoquinoline-carboxamide] was used as an antagonist of the mitochondrial or peripheral benzodiazepine receptor (mBzR), which is a component of the permeability transition pore. Whereas protection from mitochondrial dysfunction and cell injury by CsA has been used as a marker for involvement of the MPT for many years [37], CsA is also known to cause renal tubular cell apoptosis [38]. In the present study, as in the original work demonstrating inhibition of the MPT [37], we used a CsA concentration of 0.5 nmol/mg protein.…”
Section: Experimental Designmentioning
confidence: 99%
“…Apoptosis was quantified assessing the DNA content by flow cytometry using Cellquest software (BD Biosciences). 36,37 Statistical Analysis Results are presented as 25th and 75th percentiles, median, minimum, and maximum values in box plots graphics of Figures 1, 2, 4-7. In Figures 8-10, bar graphics depict mean ± s.e.…”
Section: Effect Of Rsg On Wound Healing Cell Cycle and Apoptosismentioning
confidence: 99%